2011
DOI: 10.1088/0004-6256/143/1/12
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of M Dwarf Flares on the Detection and Characterization of Exoplanets at Infrared Wavelengths

Abstract: We present the results of an observational campaign which obtained high time cadence, high precision, simultaneous optical and IR photometric observations of three M dwarf flare stars for 47 hours. The campaign was designed to characterize the behavior of energetic flare events, which routinely occur on M dwarfs, at IR wavelengths to milli-magnitude precision, and quantify to what extent such events might influence current and future efforts to detect and characterize extrasolar planets surrounding these stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 46 publications
1
17
2
Order By: Relevance
“…This magnitude of flare is in contrast to the results of Tofflemire et al [17] who expect to find flaring events in the J band occurring on mmag scales, and would transform to a u-band response of > 6, which by extrapolation of the frequencies of flaring events per magnitude found by Davenport et al [9] would be expected to be observed less than once a year.…”
Section: -P2contrasting
confidence: 77%
“…This magnitude of flare is in contrast to the results of Tofflemire et al [17] who expect to find flaring events in the J band occurring on mmag scales, and would transform to a u-band response of > 6, which by extrapolation of the frequencies of flaring events per magnitude found by Davenport et al [9] would be expected to be observed less than once a year.…”
Section: -P2contrasting
confidence: 77%
“…Stellar flares in light curves can potentially complicate the search for transits, and have even been observed during transit events themselves (Kundurthy et al, 2011). However, studies of M dwarf photometric variability on the timescales of transits conclude that stellar activity should not meaningfully affect the detection of exoplanets (Tofflemire et al, 2012;Goulding et al, 2012) (though they caution that this depends upon photometric filter and spectral type).…”
Section: Planet Detectabilitymentioning
confidence: 99%
“…∼ 5 h), a more realistic time scale and close to the maximum duration between flares observed by Pettersen et al (1984) on AD Leo. We chose this upper value, which is more likely to be representative of the occurence of flares observed by Tofflemire et al (2012); Hunt-Walker et al (2012) and of the one in lower spectral type (M0-M3) stars due to their lower magnetic activity (Kowalski et al 2009;Davenport et al 2012). We simulate a repetition of 47 flare cycles (representing ∼10 6 s s or ∼11 years).…”
Section: Chemical Compositionmentioning
confidence: 99%